Guided endodontic treatment of the upper premolar with calcification in the cervical third: A case report (Research, Society and Development, 2024)
Endodontic treatment in teeth with calcification can be a challenge, which can cause risks to the treatment such as perforations or deviations. The objective of this research was to describe, through a case report, the use of guided endodontics as a complement to access in a tooth with calcification in the cervical third. A 42-year-old female patient, she was referred for endodontic treatment of the right upper premolar. An attempt at conventional endodontic treatment was made, but without success in both canals, and thus an endodontic guide was proposed. This guide was planned and created, followed by access using a 1.3mm diameter cylindrical drill. After the canals were accessed, endodontic treatment was followed with a rotary system and completed in two sessions. The use of the surgical guide proved to be safe for accessing canals with calcification in the cervical third of upper premolars, preventing treatment failures.